The demand for U.S. railroad freight service: selected manufactured goods - Dotson, Josh (Kansas State University, 2012)
Many of the railroad demand studies are out-dated, lacking the most recent data. We felt that it is time to re-evaluate the rail markets to determine if changes have occurred in the determinants of railroad demand. This paper examines the effects of industrial production and revenue per ton of railroads on the demand for railroad service for selected manufactured goods. Also there appears to be a fundamental shift in railroad pricing after 2004. Thus a dummy variable for the 2005-2010 period was included in the model. Although there is variation in the price elasticity of demand across the manufactured goods markets, all are price inelastic.
Keywords: Railroad Demand; Staggers Act; Economics (0501); Transportation (0709)